Heroes, students, and video games at school (Research, Society and Development, 2023)
At the Educational Institution "San Cristóbal Sur Technical College," a lack of motivation in students towards their learning process has been observed. This issue is evident in the results obtained from administered knowledge tests, and through a historical tracing, these results have shown a decline. In order to address this problem, a strategy based on gamification was implemented. The aim of this strategy is to enhance learning processes, the grasp of concepts, their significance, and consequently, the acquisition of skills in the field of basic digital electronics. This was achieved through the creation and development of video games, implemented in the eighth grade.This strategy was applied to a group of students aged between 12 to 15 years old. They were tasked with creating their own video games related to the contents of Basic Digital Electronics. The strategy involved following the steps of the hero's journey and intertwining the concepts of Basic Digital Electronics with the storyline of the video game. The process of designing and building the video game required revisiting and connecting the concepts in a creative context, which significantly improved comprehension and retention.Furthermore, a progressive increase in the experimental group's results was observed compared to the control group. Additionally, a mixed methodology was implemented, demonstrating that the gamified approach coupled with the creation of video games had a positive impact on students' understanding and assimilation of the concepts.